2007
DOI: 10.1016/j.juro.2007.08.037
|View full text |Cite
|
Sign up to set email alerts
|

Is Routine Ureteral Stenting Cost-Effective in Renal Transplantation?

Abstract: Urinary anastomotic complications following renal transplantation are highly morbid. Even with modest decreases in urinary complications prophylactic ureteral stent placement is financially advantageous.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 12 publications
1
42
0
2
Order By: Relevance
“…Similarly, the costs of routine stenting compared with the costs of treating urinary leakage in a single patient showed that the cost of treating one patient with urinary leakage was the equivalent of £12 000, which was equivalent to 22 or 23 stents. 18 Thus, the authors concluded that it was financially advantageous to routinely stent patients. These studies have made some attempt at a costbenefit analysis, but there is no evidence that the cost of stent removal, anesthetic, and risks of further cystoscopy were factored into these calculations, and a more formal cost-benefit analysis would be required before any conclusions can be made.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the costs of routine stenting compared with the costs of treating urinary leakage in a single patient showed that the cost of treating one patient with urinary leakage was the equivalent of £12 000, which was equivalent to 22 or 23 stents. 18 Thus, the authors concluded that it was financially advantageous to routinely stent patients. These studies have made some attempt at a costbenefit analysis, but there is no evidence that the cost of stent removal, anesthetic, and risks of further cystoscopy were factored into these calculations, and a more formal cost-benefit analysis would be required before any conclusions can be made.…”
Section: Discussionmentioning
confidence: 99%
“…Su uso en el trasplante renal, sin embargo, sigue siendo controvertido 5,6 . Se postula que la utilización de catéter doble J podría reducir las complicaciones 2,5 , gracias a que libera a la anastomosis de la compresión extrínseca o presión intravesical 6,7 , ayuda a realizar una anastomosis más cómoda al cirujano 7 y permite reducir la presión intraureteral impidiendo la formación de fístulas 1 .…”
Section: Discussionunclassified
“…Su uso en el trasplante renal, sin embargo, sigue siendo controvertido 5,6 . Se postula que la utilización de catéter doble J podría reducir las complicaciones 2,5 , gracias a que libera a la anastomosis de la compresión extrínseca o presión intravesical 6,7 , ayuda a realizar una anastomosis más cómoda al cirujano 7 y permite reducir la presión intraureteral impidiendo la formación de fístulas 1 . Sin embargo, este tipo de catéteres no están exentos de complicaciones, especialmente en pacientes inmunodeprimidos 4 .…”
Section: Discussionunclassified